Spectroscopic and in silico approach to probe the binding interactions of irbesartan and human serum albumin - Asim Najmi; Mohammed Albratty; Hassan Ahmad Alhazmi; Neelaveni Thangavel; Md Shamsher Alam; Waquar Ahsan; Sadique Akhtar Javed; Ismail Adam Arbab; Karam Ahmed El-Sharkawy (Journal of King Saud University: Science, 2022)
Objective: The free and active concentration of drugs and thereby their pharmacokinetic properties are controlled by their binding to human serum albumin (HSA) protein. Irbesartan (IRB), an antihypertensive drug was aimed to be investigated in terms of its binding interactions with different sites of HSA using in silico molecular docking technique along with the commonly employed spectroscopic techniques. Methods: Using FT-IR spectroscopy, the spectral shifting and intensity variations before and after complexation with IRB were studied for amide A, amide-I as well as amide-II of HSA. The absorbance of HSA with and without increasing concentrations of IRB was studied at 280 nm and the binding constant was determined using UV-spectroscopy. Molecular docking study was performed, and the types of interactions were predicted. Results: The IR spectra of IRB-HSA complex showed reductions in the intensities of amide-I and II bands as well as marked reduction in the α-helix content of HSA. The absorbance of HSA protein increased with increasing concentrations of drug. A binding constant value of 5.64 × 104 M−1 was calculated indicating good interaction. Molecular docking studies showed that IRB interacts more effectively with site-I of HSA through greater number of hydrogen bonds and strong π–charge (electrostatic) interactions than with site-II. Conclusions: The spectroscopic and molecular docking techniques proved to be effective tools to study the drug-protein interaction which provided accurate results as evident from these studies. Studying drug-albumin interaction is of utmost importance as it directly influences the overall pharmacokinetics of the drugs including its distribution, metabolism and therefore the duration of action.